2023
DOI: 10.1111/bjh.19055
|View full text |Cite
|
Sign up to set email alerts
|

The Simplified Comorbidity Index predicts non‐relapse mortality in reduced‐intensity conditioning allogeneic haematopoietic cell transplantation

Shlomo Elias,
Samantha Brown,
Sean M. Devlin
et al.

Abstract: SummaryComorbidity assessment before allogeneic haematopoietic cell transplantation (allo‐HCT) is essential for estimating non‐relapse mortality (NRM) risk. We previously developed the Simplified Comorbidity Index (SCI), which captures a small number of ‘high‐yield’ comorbidities and older age. The SCI was predictive of NRM in myeloablative CD34‐selected allo‐HCT. Here, we evaluated the SCI in a single‐centre cohort of 327 patients receiving reduced‐intensity conditioning followed by unmanipulated allografts f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
0
1
Order By: Relevance
“…Shouval et al retrospectively assigned an internal and an external cohort into SCI subgroups of patients with SCI scores of 1, 2, 3, 4+, and found that increasing SCI scores directly correlated with increasing NRM. Elias et al also demonstrated greater NRM with increasing SCI in patients who underwent NMA/RIC and received allografts from matched donors ( 7 ). Unlike Shouval et al and Elias et al, however, we did not see increasing NRM with increasing SCI within individual strata, but we did see a clear increase in NRM for patients with SCI scores of 4 and greater.…”
Section: Discussionmentioning
confidence: 98%
“…Shouval et al retrospectively assigned an internal and an external cohort into SCI subgroups of patients with SCI scores of 1, 2, 3, 4+, and found that increasing SCI scores directly correlated with increasing NRM. Elias et al also demonstrated greater NRM with increasing SCI in patients who underwent NMA/RIC and received allografts from matched donors ( 7 ). Unlike Shouval et al and Elias et al, however, we did not see increasing NRM with increasing SCI within individual strata, but we did see a clear increase in NRM for patients with SCI scores of 4 and greater.…”
Section: Discussionmentioning
confidence: 98%